Measurement issues with elite athletes - Sands, W. A. (Sports Technology, 2008)
Sport science measurement presents some common and some unique challenges. Common challenges include those of funding, instrumentation availability, size and mass. Unique challenges involve working with celebrity athletes who are often reticent to serve as subjects, coaches who often will not give up training time for measurement, extraordinary demands on ease and speed of measurement and data return, and a different perspective of success in conducting research. While the academic scientist's success is usually measured in terms of publications on group data investigations, the sport scientist must improve the specific athlete(s) with whom he/she is working. For example, if an investigation of 20 athletes shows that 15 improved with the intervention, two stayed about the same and three showed worse performance results - statistical significance and/or confidence intervals would likely be achieved and the study would likely meet modern peer review standards. However, if the three athletes who got worse were the three best athletes of the group - coaches and the sport scientist will consider the intervention a failure.